Molecular and morphological evidence reveals hybridisation between two endemic cyprinid fishes. Issue 5 (22nd October 2019) - Ramoejane, Mpho; Gouws, Gavin; Swartz, Ernst R.; Sidlauskas, Brian L.; Weyl, Olaf L. F.
Abstract: The geographic occurrence of moggel Labeo umbratus × mud fish Labeo capensis hybrids and the threat of hybridisation to the genetic integrity of L. umbratus were investigated. Genetic evidence from mtDNA cytb and nDNA s7 intron sequence data indicated probable interspecific hybridisation in two impoundments, Hardap Dam (Orange River Basin, Namibia) and Darlington Dam (Sundays River Basin, Eastern Cape, South Africa). Some putative hybrids were morphologically identifiable on account of their meristic and morphometric intermediacy to the parent species. Human activities appear to drive the observed hybridisation, either through dam construction and direct stocking of L. umbratus or via translocation of Labeo capensis and the previously isolated Orange River lineage of L. umbratus into the southern‐flowing systems by inter‐basin water transfers. It is recommended that further translocation of fish from these areas should be avoided.